Urban compactness and carbon emissions: Global evidence over the period 1975-2020 - Giorgio Musto; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2024)
The share of the population living in urban centres has vastly increased in recent decades, and is predicted to further expand in the future. In this context, research on the environmental impact of different urban environments, in terms of both the form and built-up structure of cities, is particularly important to understand whether smart urban design can help mitigate the nefarious impacts of climate change. This study aims at investigating relevant associations between urban form (and specifically, urban compactness) and carbon dioxide emissions of the residential and on-road transport sectors on a global scale. The study also employs a recently established, internationally comparable definition of "urban centre", which follows population-based criteria to eliminate bias from socio-cultural or administrative factors potentially determining city boundaries. The results show that lower levels of emissions of the residential and transport sectors occur in urban environments taking on more compact shapes especially in Africa and Asia, whereas the impact of urban compactness is found to be limited in Europe and North America.
Keywords: 330